Micropropagation and monitoring of genetic stability of micropagated plantlets of Hornstedtia reticulata K. SCHUM - Bay, Hui Han (Universiti Malaysia Sarawak, (UNIMAS), 2008)
The axenic seedlings were kept in vitro as the source axenic explants. Shoot-tip explants derived from axenic off shoots were cultured in Gamborg B5 media incorporated with 30% sucrose, 3 g/L gelrite and different concentrations of cytokinins i.e. TDZ, BAP alone or in combination with NAA in the direct regeneration pathway. The primers produced amplification products which were monomorphic across the mother plants and the micropropagated plantlets, confirming the reliability of developed micropropagation protocol to produce true-to-tpe plantlets. Both leaves and leaf sheaths were used for callus induction in the indirect regeneration pathway.